Pharmaceutical and biomedical project management in a changing global environment - Babler, Scott D. (Wiley series on technologies for the pharmaceutical industry., 2010)
"This book explores some of the critical forces at work today in the complex endeavor of pharmaceutical and medical product development. Applying a structured project management framework enables companies to select and allocate the appropriate people and resources to achieve successful outcomes. The book presents chapters addressing selected issues written by experienced professionals grappling with these problems every day. Such coverage provides real-world examples of contemporary problems and their solutions"--Provided by publisher.